2023
DOI: 10.1186/s12887-023-03851-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies in the Pakistani population reveal novel associations with ventricular septal defects (VSDs)

Abstract: Background With prevalence up to 4%, Ventricular Septal Defect (VSD) is one of the leading causes of neonatal deaths. VSD is a common complex genetic disorder that has been associated with many genetic determinants. Variants from genes for the transcription factors including T-Box TBX5 and NFATc1 (nuclear factor of activated T cells, cytoplasmic 1), Vascular endothelial growth factor (VEGF), ISLET1 (encoded by the ISL1 gene) and enzyme MTHFR, a methylene tetrahydrofolate reductase were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…Our results showed that the major disorders of the VEGF pathway are related to the genes that express it. Pakistani children showed disorders in the expression of the gene encoding VEGF (17). Wang did not nd any correlation between VEGF polymorphisms and cardiac disorders by measuring several polymorphisms (27).…”
Section: Discussionmentioning
confidence: 88%
“…Our results showed that the major disorders of the VEGF pathway are related to the genes that express it. Pakistani children showed disorders in the expression of the gene encoding VEGF (17). Wang did not nd any correlation between VEGF polymorphisms and cardiac disorders by measuring several polymorphisms (27).…”
Section: Discussionmentioning
confidence: 88%